Transformational leadership-trust conversion through digital transparency and communication: a systematic review - Ednawan Prihana; Slamet Suwanto (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
This systematic review synthesizes how transformational and digital leadership are connected to public trust through organizational capability, digital transparency, dialogic communication, service performance, and procedural fairness, with Indonesia as the primary institutional context. Searches covered 2012-29 July 2026 across Google Scholar, GARUDA, publisher portals, Crossref/DOI records, and backward citations. Peer-reviewed public-sector studies with an explicit method and evidence for at least two focal constructs were eligible. Of 78 identified records, 31 were retained after screening and quality appraisal: 19 Indonesia-focused and 12 international or comparative studies. Screening, extraction, and coding were completed in two sequential passes by one reviewer using a structured evidence matrix and an MMAT-informed, design-sensitive appraisal; independent inter-rater agreement was therefore not calculated. Because designs, measures, and reported effects were not statistically comparable, narrative thematic synthesis was used instead of meta-analysis. The corpus provides stronger evidence for adjacent links than for a complete causal leadership-trust chain. Leadership is associated with internal capability and ethical climate, while trust is more consistently associated with usable and verifiable transparency, responsive communication, reliable services, and fair correction. Comparative evidence also shows that visibility, participation, or digitalization alone does not necessarily increase trust. The review proposes an evidence-informed conversion framework in which internal leadership conditions shape citizen-facing governance mechanisms that inform competence, integrity, and benevolence judgments under contextual boundary conditions.